2018
DOI: 10.1007/s10877-018-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in blood glucose concentration with intravascular microdialysis

Abstract: Blood glucose and its variability of is a major prognostic factor associated with morbidity. We hypothesized that intravenous microdialysis incorporated in a central venous catheter (CVC) would be interchangeable with changes in blood glucose measured by the reference method using a blood gas analyzer. Microdialysis and central venous blood glucose measurements were simultaneously recorded in high-risk cardiac surgical patients. The correlation between absolute values was determined by linear regression and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Intravenous microdialysis has previously been used to evaluate metabolites (e.g., lactate, glucose, pyruvate, and creatinine) [ 8 , 16 , 17 , 18 , 19 , 20 ], antibiotics (e.g., glycopeptides, aminoglycosides, and cephalosporins) [ 5 , 6 , 21 ], and antifungals (e.g., fluconazole) [ 22 ]. Studies investigating metabolites have primarily reported lower metabolite concentrations obtained by intravenous microdialysis in comparison to standard plasma sampling [ 16 , 17 , 18 , 19 , 20 ], although one study found a good correlation [ 21 ]. For flomoxef and fluconazole, comparable concentrations were found with the two sampling methods [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous microdialysis has previously been used to evaluate metabolites (e.g., lactate, glucose, pyruvate, and creatinine) [ 8 , 16 , 17 , 18 , 19 , 20 ], antibiotics (e.g., glycopeptides, aminoglycosides, and cephalosporins) [ 5 , 6 , 21 ], and antifungals (e.g., fluconazole) [ 22 ]. Studies investigating metabolites have primarily reported lower metabolite concentrations obtained by intravenous microdialysis in comparison to standard plasma sampling [ 16 , 17 , 18 , 19 , 20 ], although one study found a good correlation [ 21 ]. For flomoxef and fluconazole, comparable concentrations were found with the two sampling methods [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only few intravascular glucose monitoring techniques and devices -mainly using central venous and intraarterial access -have been tested and might overcome issues observed in subcutaneous glucose monotoring [18][19][20][21] . The few studies that directly compared the performance of intraarterial and subcutaneous CGM show conflicting results: one study showed superior performance of the intraarterial system whereas the other study showed comparable performance 22,23 .…”
mentioning
confidence: 99%
“…Reported accuracy data on central venous catheter based continuous glucose monitoring varies largely between studies and use of different accuracy metrics make a comparison difficult 18,22,24 . It can be hypothesized that the superior performance of systems using the intravascular rather than the subcutaneous space can be attributed to the physiological lag-time between compartments also seen in non-critical illness but might be aggrieved due to alterations in subcutaneous microcirculation in critically illness and largely depend on tissue perfusion 15,25 .…”
mentioning
confidence: 99%